Studie av projektet Skeppsbron på Södra Älvstranden med hjälp av Autodesk Ecotect - Viklund Tallgren, Mikael (My University, 2010)
The underlying problem in this thesis is the number of consultants that is needed at an early stage in city planning. The scope of this thesis is to investigate the possibility to reduce the number of consultants active in the different analyses. The method to do this was to make use of Ecotect, an analysis tool that was recently acquired by Autodesk. The program gathers several different methods of analysis in one single tool. The hope was to gather four different analysis methods in one program and by that reduce the number of consultants. A 3d-model was acquired from one of the consultants, this model was then used to the investigations. Apart from Ecotect three more programs was used. The three programs used where SketchUp, for export of the model to Ecotect, Winair 4 and partly NIST FSD for wind simulations. The goal was to be able to compare the results that the consultants got with the results acquired by Ecotect. In the end it the conclusion was that Ecotect only could do three out of the original four analyses. Out of the three analyses, two could be done directly in Ecotect and one could visualize the results of an external program. The three analysis methods were Massing, solar/shadow and Wind analysis. The wind analysis was available via an export of data and an import and visualization of the calculation. The conclusion about the three methods was generally that Ecotect produce similar if not identical results in both massing and solar/shadow analysis. In the wind analysis the results generated the same conclusions but differed some in wind orientation over the chosen period. In an deeper study with weather data form an external source the results came up very similar and very little or none difference could be observed. The two CFD-programs used (WinAir 4 and NIST FSD) were either hard to get hold of or hard to understand. In the analysis’s here WinAir 4 was used due to the complexity of NIST FSD. The downside of WinAir 4 was a limited number of analysis nodes. This limited the analysis to be either very general (few points in a big area) or very specific (lots of points in a small area). The conclusion of this thesis is that there is still a lot of connection to other programs and that the analysis’s could only be done partly in Ecotect.
Keywords: Hållbar utveckling; Building Futures; Samhällsbyggnadsteknik; Sustainable Development; Building Futures; Civil Engineering